Polymerization‐Induced Self‐Assembly Providing PEG‐Gels with Dynamic Micelle‐Crosslinked Hierarchical Structures and Overall Improvement of Their Comprehensive Performances - Chang, Zi‐Xuan; Hong, Chun‐Yan; Zhang, Wen‐Jian (Macromolecular rapid communications., 2025)
Polymer gels are fascinating soft materials and have become excellent candidates for wearable electronics, biomedicine, sensors, etc. Synthetic gels usually suffer from poor mechanical properties, and integrating good mechanical properties, adhesiveness, stability, and self‐healing performances in one gel is more difficult. Herein, polymerization‐induced self‐assembly (PISA) providing PEG‐gels with an overall improvement in their comprehensive performances is reported. PISA synthesis is carried out in PEG (solvent) to efficiently produce various nanoparticles, which are used as the nanofillers in the subsequent synthesis of PEG‐gels with dynamic micelle‐crosslinked hierarchical structures. Compared to hydrogels, PEG‐gels show excellent long‐term stability due to the nonvolatile feature of PEG solvent. The hierarchical PEG‐gels (with nanofillers) exhibit better mechanical and adhesive properties than the homogeneous‐gels (without nanofillers). The energy dissipation mechanism of the PEG‐gels is analyzed via stress relaxation and cyclic mechanical tests. High‐density hydrogen bonds between the micelles and PAA matrix can be broken and reformed, endowing better self‐healing properties of the dynamic micelle‐crosslinked PEG gels. This work provides a simple strategy for producing hierarchical structural gels with enhanced properties, which offers fundamentals and inspirations for the designing of various advanced functional materials. In this work, PISA synthesis is carried out in PEG (solvent) to efficiently produce various nanoparticles, which are used as the nanofillers in the subsequent synthesis of PEG‐gels with dynamic micelle‐crosslinked hierarchical structures. The hierarchical PEG‐gels (with nanofillers) exhibit better mechanical and adhesive properties than the homogeneous‐gels (without nanofillers).